Anticancer Drug Camptothecin Test in 3D Hydrogel Networks with HeLa cells - Liang, J.; Sun, Xiuzhi Susan; Yang, Zhilong L.; Cao, S. (My University, 2017)
Development of a biomimetic 3D culture system for drug screening is necessary to fully understand the in vivo environment. Previously, a self-assembling peptide hydrogel has been reported; the hydrogel exhibited physiological properties superior to a 3D cell culture matrix. In this work, further research using H9e hydrogel with HeLa cells was carried out considering H9e hydrogel's interaction with camptothecin, a hydrophobic drug. According to AFM images, a PGworks solution triggered H9e hydrogel fiber aggregation and forms a 3D matrix suitable for cell culture. Dynamic rheological studies showed that camptothecin was encapsulated within the hydrogel network concurrently with peptide self-assembly without permanently destroying the hydrogel's architecture and remodeling ability. Fluorescence measurement indicated negligible interaction between the fluorophore part of camptothecin and the hydrogel, especially at concentration 0.25 and 0.5 wt%. Using a dialysis method, we found that H9e hydrogel could not significantly inhibit the diffusion of camptothecin encapsulated inside the hydrogel matrix. In the cell culture experiment, HeLa cells were simultaneously embedded in the H9e hydrogel with the initialization of hydrogelation. Most importantly, cell viability data after camptothecin treatment showed responses that were drug-dose dependent but unaffected by the H9e hydrogel concentration, indicating that the hydrogel did not inhibit the drug.
Citation: Liang, J., Sun, X. S., Yang, Z. L., & Cao, S. (2017). Anticancer Drug Camptothecin Test in 3D Hydrogel Networks with HeLa cells. Scientific Reports, 7, 9. doi:10.1038/srep37626
Keywords: Bovine Serum-Albumin; Acid-Based Hydrogels; In-Vitro; Extracellular-Matrix; Peptide Hydrogels; Breast-Cancer